An Integrative Model of Carbon and Nitrogen Metabolism in a Common Deep-Sea Sponge (Geodia barretti) - de Kluijver, Anna; Bart, Martijn C.; van Oevelen, Dick; de Goeij, Jasper M.; Leys, Sally P.; Maier, Sandra R.; Maldonado, Manuel; Soetaert, Karline; Verbiest, Sander; Middelburg, Jack J. (Frontiers in Marine Science, 2021)
Deep-sea sponges and their microbial symbionts transform various forms of carbon (C) and nitrogen (N) via several metabolic pathways, which for a large part are poorly quantified. Previous flux studies on the common deep-sea sponge Geodia barretti consistently revealed consumption of dissolved organic carbon (DOC) and oxygen, and release of nitrate. Here we present a biogeochemical metabolic network model that for the first time quantifies C and N fluxes within the sponge holobiont in a consistent manner, including many poorly constrained metabolic conversions. Using two datasets, covering a range of individual G. barretti sizes (10-3500 ml), we found that the variability in metabolic rates partially resulted from body size, as O2 uptake allometrically scales with sponge volume. Our model analysis confirmed that dissolved organic matter (DOM), with an estimated C:N ratio of 7.7 ± 1.4, is the main energy source of G. barretti. DOM is primarily used for aerobic respiration, then for dissimilatory NO3- reduction to NH4+ (DNRA), and, last, for denitrification. Dissolved organic carbon (DOC) production efficiencies (production/assimilation) were estimated as 24 ± 8 % (larger individuals) and 31 ± 9 % (smaller individuals), so most DOC was respired to CO2, which was net released in a ratio of 0.77 - 0.81 to O2 consumption. Internally produced NH_4^+ from cellular excretion and DNRA fueled nitrification. Nitrification, associated chemoautotrophic production, contributed 5.1 - 6.7 ± 3.0 % to total sponge production. While overall metabolic patterns were rather independent of sponge size, (volume-) specific rates were lower in larger sponges compared to smaller sponge. Specific biomass production rates were 0.16 % d-1 in smaller compared to 0.067 % d-1 in larger G. barretti, as expected for slow-growing deep-sea organisms. Collectively, our approach shows that metabolic modelling of hard-to-reach, deep-water sponges can result in accurate predictions of community-based respiration and production that will facilitate further investigations on the functional integration and the ecological significance of the sponge aggregations in the deep-sea ecosystems.